Translanguaging Practices in Primary Education: A Systematic Literature Review of Pedagogical Trends - Muhammad Gazali; Suyono Suyono; Ade Eka Anggraini; Khairun Nisa (Universitas Muhammadiyah Makassar, 2026)
This systematic literature review examines research trends and pedagogical implications of translanguaging practices in primary education. Drawing on 148 Scopus-indexed publications published between 2015 and 2025, the study analyzes annual publication trends, geographical distribution, research designs, participant focus, developed skills, and students’ linguistic backgrounds. The findings indicate a substantial increase in translanguaging research over the past decade, reflecting a growing recognition of translanguaging as a pedagogical response to multilingual classroom realities in primary education. Research output is predominantly concentrated in a limited number of countries, particularly Spain, the United States, China, and South Africa, revealing imbalances in global knowledge production. Methodologically, qualitative approaches dominate, with students identified as the primary research subjects, underscoring the learner-centered orientation of translanguaging pedagogy. The reviewed studies report that translanguaging supports language development, classroom communication, conceptual understanding, and the legitimization of students’ mother tongues within instructional practices. Translanguaging is most frequently implemented among EFL learners, immigrant students, indigenous communities, and learners in complex multilingual contexts. Overall, this review positions translanguaging as a pedagogical approach that extends beyond linguistic outcomes, offering meaningful implications for inclusive language teaching practices and the sustained use of learners’ linguistic resources in multilingual primary classrooms.